Is individual nasal sensitivity related to cellular metabolism of formaldehyde and susceptibility towards formaldehyde-induced genotoxicity? - Zeller, Jasmin; Ulrich, Alexandra; Müller, Jörg U.; Riegert, Clarissa; Neuss, Simone; Bruckner, Thomas; Triebig, Gerhard; Speit, Günter (Mutation research. Genetic toxicology and environmental mutagenesis, 2011)
Forty-one volunteers (male non-smokers, aged 32±9.6yrs) were tested for susceptibility towards unspecific nasal irritation (sensitivity towards CO2) in order to define subgroups of hypersensitive and hyposensitive subjects. Blood samples were taken and the expression (mRNA level) of the GSH-dependent formaldehyde dehydrogenase gene (FDH, identical to alcohol dehydrogenase 5, ADH5; EC 1.2.1.46) was measured in leukocytes by quantitative real-time RT-PCR with TaqMan probes. FDH is the most important enzyme for the metabolic inactivation of FA. Blood samples were exposed to 150μM formaldehyde (FA) for 2h and the induction of DNA-protein crosslinks (DPX) in leukocytes was measured by means of a modification of the alkaline comet assay (i.e., by assessing the reduction of DNA migration induced by γ-radiation). Removal of DPX was determined by the abolition of FA-induced reduction in DNA migration within 4h after the end of the exposure. Furthermore, the induction of sister chromatid exchange (SCE) in cultured lymphocytes was studied after treatment of whole blood cultures with FA (150μM). A correlation analysis was performed for all parameters tested for the whole study group and for hypersensitive and hyposensitive subgroups. The results indicate that despite large differences in CO2-sensitivity, the susceptibility towards nasal irritation was not related to the induction of genotoxic effects (DPX, SCE) in peripheral blood or to the protection of blood cells against FA-induced effects (expression of FDH, repair capacity for FA-induced DPX). There was no correlation between CO2-sensitivity and the expression of FDH. There was also no close correlation between the various indicators of cellular sensitivity towards FA-induced genotoxic effects and no subgroups were identified with particular mutagen sensitivity towards FA.
Gesehen am 22.12.2022